Pelaksanaan Supervisi Akademik untuk Meningkatkan Kompetensi Guru dalam Menerapkan Model Pembelajaran Berbasis Teknologi di Sekolah Binaan SMPN 6 Tanjung Jabung Timur Semester Genap Tahun Ajaran 2021/2022 - Jaliusril Jaliusril (Journal on Education, 2023)
This study aims to obtain information and discuss the implementation of academic supervision to increase teacher competency in implementing technology-based learning models in target schools of SMPN 6 Tanjung Jabung Timur even semester of the 2021/2022 academic year. This type of research is school action research. This research was conducted at SMPN 6 Tanjung Jabung Timur which is a school assisted by researchers as supervisors. This research schedule is carried out in the even semester of the 2021/2022 school year with 8 teachers as subjects. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use percentages and data reduction. Based on the results of the research and discussion, it can be concluded that through the implementation of academic supervision, it can increase teacher competence in applying technology-based learning models at SMPN 6 Tanjung Jabung Timur target schools in the even semester of the 2021/2022 school year. This can be seen from the increase in the teacher's ability to apply the learning model from cycle I to cycle II.